Field evaluation of the Cepheid GeneXpert Chlamydia trachomatis assay for detection of infection in a trachoma endemic community in Tanzania. - Alexander Jenson; Laura Dize; Harran Mkocha; Beatriz Munoz; Jennifer Lee; Charlotte Gaydos; Thomas Quinn; Sheila K West (Public Library of Science (PLoS), 2013)
To determine the sensitivity, specificity, and field utility of the Cepheid GeneXpert Chlamydia trachomatis (CT) Assay (GeneXpert) for ocular chlamydia infection compared to Roche Amplicor CT assay (Amplicor).In a trachoma-endemic community in Kongwa Tanzania, 144 children ages 0 to 9 were surveyed to assess clinical trachoma and had two ocular swabs taken. One swab was processed at Johns Hopkins University, Baltimore MD, using Amplicor, (Roche Molecular Diagnostics) and the other swab was processed at a field station in Kongwa using the GeneXpert Chlamydia trachomatis/Neisseria gonorrhoeae assay (Cepheid). The sensitivity and specificity of GeneXpert was compared to the Amplicor assay.Of the 144 swabs taken the prevalence of follicular trachoma by clinical exam was 43.7%, and by evidence of infection according to Amplicor was 28.5%. A total of 17 specimens (11.8%) could not be processed by GeneXpert in the field due to lack of sample volume, other specimen issues or electricity failure. The sensitivity of GeneXpert when compared to Amplicor was 100% and the specificity was 95%. The GeneXpert test identified more positives in individuals with clinical trachoma than Amplicor, 55% versus 52%.The GeneXpert test for C. trachomatis performed with high sensitivity and specificity and demonstrated excellent promise as a field test for trachoma control.